Evaluation of Pastoral Counseling and Accompaniment Services for Increasing Children's Sense of Self- Esteem at GMIT Getsemani Tarus Timur Regency Kupang - Yenry Anastasia Pellondou; Debby Yunita Mada; Marleny Rambu Riada; Ferdinan S.E. Lasibey (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
This study aims to evaluate the pastoral counseling and mentoring services for enhancing the self-esteem of children in the PAR community at the Evangelical Christian Church in Timor (GMIT) Getsemani, East Tarus, Kupang Regency. The mentoring and pastoral counseling services can significantly contribute to improving the self-esteem of PAR children. This study employs a descriptive qualitative method to assess the role of pastors and presbyters in the services provided. Limitations in evaluating the mentoring and pastoral counseling services, especially regarding the long-term impact on improving the self-esteem of PAR children, pose a challenge in this research. This study found that there is a shortage of professional personnel in providing mentoring and pastoral counseling services, besides pastors. Therefore, based on the results of the evaluation conducted with the pastor, this research suggests the need for follow-up activities for presbyters (teachers) of PAR in necessary follow-up activities, namely training of trainer (TOT). Recommendations obtained from the results of this evaluation indicate that the self-esteem issues of PAR children at GMIT Getsemani Tarus Timur, Kupang Regency, require both basic and advanced training for presbyters (teachers) who serve PAR children with self-esteem problems.